GENETIC EPISTEMOLOGY, FROM JEAN PIAGET’S OWN WORDS AND WORKS - Ricardo Pereira Tassinari (Kínesis)
The principal intention and meaning of Jean Piaget’s work is difficult to grasp, particularly due to its great length and depth, and some widely spread general misconceptions about it. In order to help clarify it, and furnish data for the discussions about it, this article aims to expose and clarify, in general lines, Piaget’s main project: Genetic Epistemology. The intention here is to point out its motive and constitution, from Piaget’s own published works and words. In the end, the data analysis shows that the main intention and meaning of Piaget’s work was to build a new chapter in Epistemology, Theory of Knowledge and Philosophy of Science, founding and establishing Genetic Epistemology: a new inter-, trans- and multidisciplinary area, directly bound to the scientific methods and contents, and their geneses, especially related to Genetic and Cognitive Psychologies and History of Science. As the outcome, this area furnished various studies of scientific notions and concepts, including their geneses, many analyses of the methods of various sciences, and studies on the System of Sciences, as well as more detailed studies of the elements necessary for the acquisition of knowledge, with concepts so close to the experience that they are immediately applicable.